Case Report: Autoimmune hepatitis in a patient with pseudohypoaldosteronism type 1—insights into a rare co-occurrence - Al Thiabat, Hanan; Alsheyyab, Jafar; Khalid, Israa Waleed; Abdel Razzaq, Rafeef; Barham, Kamleh; Algharaibeh, Hanaa M.; Altamimi, Eyad (Frontiers in Pediatrics, 2025)
BackgroundPseudohypoaldosteronism (PHA) type 1 is a rare disease characterized by an end-organ unresponsiveness to mineralocorticoids, which results in salt loss from the kidney and impaired potassium and hydrogen secretion. It is subdivided into two main types: renal PHA and systemic PHA, which vary in presentation and severity.Case reportOur patient presented at the age of 1 month with fever and vomiting, electrolyte disturbances, hyponatremia, hyperkalemia, and metabolic acidosis. The infant was later diagnosed with PHA type 1 caused by a mutation of SCNN1A, and she had persistent elevation of liver enzymes, for which she was diagnosed with autoimmune hepatitis. She was initially treated with sodium supplements, sodium bicarbonate, and ion exchange resin (calcium polystyrene sulfonate); subsequently, prednisolone and azathioprine were added.ConclusionWe report a unique clinical presentation involving a patient who was diagnosed at the age of 1 month with PHA type 1 caused by a mutation of SCNN1A and who was diagnosed with autoimmune hepatitis. The coexistence of these two conditions could highlight a potential shared pathological pathway. Further research into the genetic and immunological links between these rare disorders is warranted.